A 10‐Year Analysis of Head and Neck Injuries Involving Nonpowder Firearms. (1st March 2017) - Dandu, Kartik V.; Carniol, Eric T.; Sanghvi, Saurin; Baredes, Soly; Eloy, Jean Anderson
Abstract : Objectives: Firearms have an enduring and visible presence within American culture. However, the public health impact of nonpowder firearms and other "toy" guns has not been fully studied. These guns—including BB guns (ie, ball bearing), paintball guns, and pellet guns—are typically marketed to a younger audience. The objective of this study is to analyze head and neck injuries related to nonpowder firearms. Study Design: Cross‐sectional analysis of a national database. Setting: Academic medical center. Subjects and Methods: The National Electronic Injury Surveillance System was queried for head and neck injuries involving nonpowder guns, including air, BB, and pellet guns, and associated ammunition. Analysis of age, sex, incidence, injury location, and diagnosis was performed. Results: From 2005 to 2014, there were 1695 cases recorded, or 55, 060 estimated emergency room visits, due to injuries related to nonpowder guns and fired ammunition. The majority of patients were male (80.9%). These injuries were most common in children 6 to 12 years of age (37.9%), followed by those 13 to 18 years old (27.1%) and adults (≥19 years old; 17.8%), while preschool children (0‐5 years) represented 17.2%. The most common injury diagnosis was penetrating foreign body (34.9%), followed by lacerations (24.3%) and contusions/abrasions (13.7%). Conclusion: Nonpowder and other nonlethal firearm‐related injuries to the head and neck region are a frequent source of emergency room visits nationally. Safety measures and public education on a mainstream level are required.